An Exploration of Life and Career Narratives of Black Senior Managers: The Storied Habitus of Career Navigation - Ramodibe, Refiloe (University of the Witwatersrand, Johannesburg, 2023)
This research located black senior managers within a temporal frame that links them with their families, communities, childhoods, socio-political and economic histories. This location shed new light since it illuminated their lives and careers in new ways that are grounded in history and context. It enabled an understanding of black senior managers as bearing histories that they bring along with them into the workplace. To explore the stories of these senior managers, I conducted in-depth narrative interviews with twenty black men and black women who occupy senior positions within the financial services sector. Accessing these histories through the genre of narrative assisted in showcasing what is enabled by storying one’s life, therefore creating circuits of meaning-making that connect seemingly disparate sites of the personal, historical, social and workplace. At its core then, this project was about storying the early lives of black senior managers by locating them as mostly working class, caught up in the struggles against apartheid for democratisation, as benefiting from the opportunities enabled by the transition to democracy, as entering the white and masculine corporate workplace of the financial services sector, and as reaching and navigating seniority in their organisations. The participant’s narratives were read through the lenses of narrative theory, habitus, the black feminist theory of intersectionality, and critical race theory. The basic assumption of habitus is that the way one acts and behaves is influenced by where one comes from and one’s dispositions, including contextually salient identity categories, such as race, class, and gender. The basis of these theories is the assumption that there might be a difference in how people of varying class backgrounds and black men and women narrate their stories of mobility. The stories told by participants highlighted the role of the senior managers’ habitus in shaping their identities and trajectories. Childhood experiences and parental influences were found to have shaped their later behaviours in navigating their career journeys. Access to mentors and sponsors early on in their careers was found to have provided the senior managers with the capital that allowed them to progress to more senior roles. Refuting the existing narrative that black people move between organisations excessively, senior managers’ tenure illustrated that they stayed in their organisations for longer periods than industry norms. Notwithstanding their tenure, their stories suggest that unaccommodating cultures and unconscious bias remain prevalent in the financial services sector. Organisations that had more black people in senior roles were found to drive the transformation agenda iv more intentionally. The black senior managers understood their role as that of influencing the cultures of their organisations while also paying it forward by driving the transformation agenda. In the process of sharing their life and career stories, the black senior managers articulated their experiences and understanding of themselves, others, and the world. Therefore, not only did the personal narratives enlighten us about the participants’ personal and working lives, but they illuminated how their identities as black senior managers working within the financial services sector were shaped over time. A prominent finding from the study was that while the black senior managers shared similar experiences related to race, their experiences differed in terms of their family backgrounds and schooling experiences in their childhood. Black people’s experiences may be common in certain aspects and different in others. This necessitates the importance of exploring heterogeneity in organisational studies. This study contributes to organisational studies, gender and critical race studies, history and social theory.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023
Keywords: UCTD; Narrative; Race; Gender; Equality; Careers; SDG-5: Gender equality; SDG-8: Decent work and economic growth